Delay in seeking medication for oral cancer and its influencing factors – a review of research progress - Yuanyuan YANG; Jiegang HUANG; Huaming MAI; Qingsi OUYANG (Zhongguo gonggong weisheng)
Oral cancer, a common malignancy of the head and neck, is a major public health concern due to its high incidence and low five-year survival rate. Treatment and prognosis are influenced by several factors, with timely medical consultation being of paramount importance. Studies have shown that delays of more than three months between the onset of symptoms and seeking medical attention significantly increase the risk of oral cancer progression to advanced stages. This paper provides a comprehensive review of the current literature on delayed medical consultation in oral cancer patients, both nationally and internationally. It analyzes various factors that may influence patient behavior, including oral cancer awareness and knowledge, psychosocial variables, health literacy, socioeconomic status, and oral examination habits. It also examines the role of screening programs in increasing early detection rates. This review provides valuable insights for understanding and addressing the issue of delayed medical consultation among oral cancer patients in China, and provides a basis for developing effective prevention and control strategies.